Indicadores do Programa Nacional de Imunizações em Menores de um ano: Maranhão, 2010 a 2021 - MARINHO, Cleia Varão (2022)
This study aimed to analyze the indicators of the National Immunization Program (PNI) for children under one year old and classify the municipalities regarding the risk of transmission of immunopreventable diseases in Maranhão from 2010 to 2021. This is an ecological, longitudinal, temporal series study, with state scope, considering all 217 municipalities in Maranhão over a period of 12 years (2010 to 2021). The PNI indicators for the state were: Vaccination Coverage (CV), Homogeneity of Vaccination Coverage (HCV), Proportion of Abandonment (PA). The classification of the risk of disease transmission, carried out in the 217 municipalities, was: very low, low, medium, high and very high risk. The results pointed to fluctuating and discrepant CV among vaccines, with a downward trend in the state. During the historical series, the sharpest drop was for the yellow fever vaccine (54.2%). All HCV rates were below the parameter established by the Ministry of Health, with a decrease from the year 2014. The highest PA was for the Pentavalent vaccine in the year 2020 (37,5%). When comparing the risk of transmission of immunopreventable diseases among the 217 municipalities of Maranhão, at the beginning (year 2015) and at the end of the historical series (year 2021), it was verified that there was an increase of 52,5% of municipalities with very high and high risk classifications. It was concluded that in the period from 2013 to 2021, there was a progressive worsening in the PNI indicators in the state of Maranhão and only two of the ten vaccines had achieved the recommended CV targets and when analyzing the last two years, none of the vaccines reached the goal. For the improvement of these indicators, it is important to take more effective actions both in terms of health actions and services and in management (local, state and national) with repercussions on collective health for the entire population. Emphasis on popular health education and reduction of missed vaccination opportunities is recommended. The research findings can help managers in the analysis of the main indicators of the PNI, especially in view of the pandemic scenario of recent years.